2022
DOI: 10.1155/2022/5813522
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Model and Immune Infiltration of Ferroptosis Subcluster-Related Modular Genes in Gastric Cancer

Abstract: Background. Gastric cancer (GC) is one of the gastrointestinal tumors with the highest mortality rate. The number of GC patients is still high. As a way of iron-dependent programmed cell death, ferroptosis activates lipid peroxidation and accumulates large reactive oxygen species. The role of ferroptosis in GC prognosis was underrepresented. The objective was to investigate the role of ferroptosis-related genes (FRGs) in the prognosis and development of GC. Methods. Datasets of GC patients were obtained from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…In addition to being expressed in CAFs, GFPT2 is also expressed in tumor parenchymal cells. The high expression of GFPT2 is closely related to invasion, metastasis, drug sensitivity, and poor prognosis of a variety of tumors including lung cancer [ 124 , 125 ], epithelial ovarian cancer [ 126 128 ], CRC [ 129 ], breast cancer [ 130 , 131 ], GC [ 132 ] and leiomyosarcoma [ 133 ].…”
Section: Caf Markers With Cancer Promotionmentioning
confidence: 99%
“…In addition to being expressed in CAFs, GFPT2 is also expressed in tumor parenchymal cells. The high expression of GFPT2 is closely related to invasion, metastasis, drug sensitivity, and poor prognosis of a variety of tumors including lung cancer [ 124 , 125 ], epithelial ovarian cancer [ 126 128 ], CRC [ 129 ], breast cancer [ 130 , 131 ], GC [ 132 ] and leiomyosarcoma [ 133 ].…”
Section: Caf Markers With Cancer Promotionmentioning
confidence: 99%
“…Excitingly, a range of gene models centered around programmed cell death (such as ferroptosis and cuprotosis) have been developed. [21][22][23][24][31][32][33] These models hold great promise in identifying potential targets for therapeutic interventions in GC.…”
Section: Discussionmentioning
confidence: 99%
“…This area represents a new research direction in GC. [21][22][23][24] One novel and less explored mechanism of programmed cell death is the discovery of disulfidptosis this year. Researchers have observed that during glucose starvation, an abnormal accumulation of intracellular disulfide bonds disturbs the normal disulfide bonds between cytoskeletal proteins, ultimately leading to cell death.…”
Section: Introductionmentioning
confidence: 99%
“…1E). Among the top 10 hub mRNAs in the PPI network displayed using STRING, jun proto-oncogene, C-X-C motif chemokine ligand 8, epiregulin, cyclin-dependent kinase inhibitor 1A, serpin family E member 1 and DNA damage-inducible transcript 3 were previously reported to be involved in ferroptosis (45)(46)(47)(48)(49)(50), suggesting that the remaining four genes, growth arrest and DNA damage inducible α (GADD45A), epithelial mitogen (EPGN), heparin-binding EGF-like growth factor (HBEGF) and transforming growth factor α (TGFA), may also have roles in ferroptosis (Fig. 1F and G).…”
Section: Identification Of Demrnas Involved In Regulating Ferroptosismentioning
confidence: 99%